2016
DOI: 10.1177/0954410016630565
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the unsteady behaviors and rotating stall inception process in a counter-rotating axial compressor

Abstract: Unsteady computations of a counter-rotating axial compressor are performed and analyzed to investigate the unsteady behaviors in the compressor and the role of the tip leakage flow together with the rotating stall inception process. The results show that the oscillation on the pressure side is much stronger than that on the suction surface for both rotors, especially near the tip region where the trajectory of the tip leakage vortex (TLV) interacts with the blades most often. There exists a periodical leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…Past research on this compressor has indicated that the TLF from near the mid-chord plays a more important role in the generation of the self-induced unsteadiness of the TLF [37,38]. In the current paper, the result shows that it is more effective to improve the flow stability by controlling the critical TLF released from near the mid-chord.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…Past research on this compressor has indicated that the TLF from near the mid-chord plays a more important role in the generation of the self-induced unsteadiness of the TLF [37,38]. In the current paper, the result shows that it is more effective to improve the flow stability by controlling the critical TLF released from near the mid-chord.…”
supporting
confidence: 49%
“…For example, a circumferential groove with its leading edge positioned at 20% tip axial chord length downstream of the blade leading edge is named G2. Previous research on this compressor has indicated that the flow fields in the tip region of R2 are responsible for the spike-type flow instability of the CRAC [35,37,38]. Therefore, different circumferential single grooves over the blade tip of R2 were numerically investigated in the current paper.…”
Section: Compressor Geometry and Ct Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous researches showed that the flow field in the tip region of R2 is responsible for the spike-type flow instability of the CRAC. 26,29 Therefore, the impact of TLF from R1 becomes more and more significant due to the increase of TCS, which plays an important role in the deterioration of the performance of both R2 and the counter-rotating stage because of the rotor–rotor interaction effect. The analysis above shows that there are two aspects of influence from the increase of TCS.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that there are many fresh characteristics and unique flow phenomena in CRAC compared with the conventional compressors. 2229…”
Section: Introductionmentioning
confidence: 99%